2005
DOI: 10.1002/ppul.20175
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein expression is increased in the ipsilateral but not contralateral lungs of fetal sheep with left‐sided diaphragmatic hernia

Abstract: Congenital diaphragmatic hernia (CDH) impairs fetal lung growth and increases the density of alveolar epithelial type 2 (AE2) cells. There is controversy whether surfactant protein (SP) expression is altered in CDH. The primary aim of this study was to assess SP expression (mRNA and protein) in the left and right lungs of fetal sheep with and without a diaphragmatic hernia (DH). Left-sided DH was created in four fetal sheep at 65 days of gestational age (g.a.). Sham-operated animals were used as controls. At 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 54 publications
2
16
1
Order By: Relevance
“…Expansion (in LMBO) or compression (in CDH or on the right side in LMBO) of the fetal lungs in our study generates mechanical cell deformations and alters the density of AE2 cells. These observations support that mechanical stress experienced by AEC influences AE2 cell density and the premise that fetal lung hypoplasia favors an AE2 phenotype [39]. In the present study, we did not measure type 1 cell density that would be required to further investigate AEC differentiation in LMBO.…”
Section: Discussionsupporting
confidence: 56%
“…Expansion (in LMBO) or compression (in CDH or on the right side in LMBO) of the fetal lungs in our study generates mechanical cell deformations and alters the density of AE2 cells. These observations support that mechanical stress experienced by AEC influences AE2 cell density and the premise that fetal lung hypoplasia favors an AE2 phenotype [39]. In the present study, we did not measure type 1 cell density that would be required to further investigate AEC differentiation in LMBO.…”
Section: Discussionsupporting
confidence: 56%
“…(7) Lastly, our DH model uses a left diaphragm defect and we analyzed the lateral aspect of the left upper lobe. While other investigators have shown similar gene expression profiles in left and right lungs after left or right DH (7,9,10), one paper did report differences in surfactant gene expression between right and left lungs (12). We did not perform validation experiments comparing right and left lungs.…”
Section: Discussionmentioning
confidence: 99%
“…While TO for CDH may gain more widespread acceptance in the coming years, there remains an urgent need to understand the cellular responses to CDH and TO so that targeted therapies may be developed to improve fetal lung development and to limit any undesirable effects of TO. There have been reports of how CDH and TO impact lung matrix synthesis (6)(7)(8)(9), lung epithelial function and surfactant (10)(11)(12)(13) and microvascular development (14)(15)(16), and that tracheal occlusion reverses some of resulting in severe pulmonary hypoplasia (2). Despite optimal medical and surgical care, mortality remains high with survivors experiencing severe restrictive lung disease and significant pulmonary hypertension (1).…”
mentioning
confidence: 99%
“…This conclusion was based on a variety of determinations, including tissue and lavage-fluid phospholipids, lavage-fluid SPs, tissue SP and SP-transcript levels, and dynamic surface-tension measurement. However, conflicting results have been published indicating no change in alveolar surfactant composition [21], unchanged or even increased SP expression with a higher proportion of cells expressing SP in the nitrofen model [22,23], and increased SP expression in the ovine model [24]. …”
Section: Introductionmentioning
confidence: 99%